Why do Malaysian customers patronise Islamic banks? - Abdullah, Nurdianawati Irwani; Dusuki, Asyraf Wajdi (Emerald Group Publishing Limited, 2007)
Purpose – The purpose of this paper is to examine the main factors that motivate customers to deal with Islamic banks particularly in a dual banking environment, like in the case of Malaysia. A discussion on factors relating to corporate social responsibility initiatives as part of potential customers’ banking selection criteria is also included. Design/methodology/approach – The paper presents primary data collected by self-administered questionnaires involving a sample of 750 respondents from four different regions in Malaysia. The Islamic banking criteria ranking as perceived by the respondents are analysed using Friedman Test. To further explore the customers’ understanding of the banking criteria, an exploratory factor analysis is employed. Findings – This study reveals that the selection of Islamic banks appears to be predominantly a combination of Islamic and financial reputation and quality service offered by the bank. Other factors perceived to be important include good social responsibility practices, convenience and product price. Practical implications – The empirical evidence of this paper affects two aspects; first, Islamic banks must offer quality services while maintaining its Islamic credential and reputation; second, Islamic banks should also embrace good customers services policies to reap its potential as a strategic tool to achieve competitive advantage, enhance reputation and secure customers allegiance. This research will be of interest to both incumbent and potential entrants into this niche market. Originality/value – The paper reports findings from the first nationwide study carried out in the area of Islamic banking selection criteria.